The contribution of trade openness to health outcomes in sub-Saharan African countries: A dynamic panel analysis - Mwoya Byaro; Juvenal Nkonoki; Hozen Mayaya (Research in Globalization, 2021)
This study examines the contribution of trade openness to health outcomes (measured in terms of under-five mortality and life expectancy) in 33 sub-Saharan African countries using a two-step system Generalized Methods of Moments (GMM) estimator over the year 2000-2016, while controlling for endogeneity of variables (i.e. omitted variables bias and reverse causality). The findings show that, trade openness and measles vaccination reduces under-five mortality in the region. The findings reveal that, trade openness, income (GDP per capita), and health financing (total public and private health expenditure) all contribute to a longer life expectancy. Overall, it was found that trade openness is statistically significant and contributes to health improvement (i.e. under-five mortality and life expectancy). This implies that the health sector in sub-Saharan African countries is not at risk as a result of increased trade. However, the study recommends easing and increasing trade to allow governments to obtain more financial resources to improve the welfare of their people, to include health professionals in future trade negotiations and agreements for public health benefits, and take steps to remove import duties on health related products. These findings have significant implications for sub-Saharan Africa, as well as other developing countries.
Keywords: 330; Trade openness; GMM; Instruments; Health outcomes